What determines foreign aid to Papua New Guinea? An inter-temporal model of aid allocation - Simon Feeny (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper models the inter-temporal allocation of foreign development aid to Papua New Guinea (PNG). A formal theoretical model of aid allocation is developed, in which aid to any one country is determined jointly with aid to all other recipient countries. This is recognized in the econometric application of this model, which simultaneously models aid to number of countries in addition to PNG. Results based on data for the period 1969 to 1998 indicate that both recipient need and donor interest variables determine the amount of Australian and total foreign aid to PNG and most other countries under consideration.
Keywords: C30; F35; 330; foreign aid; allocation; Papua New Guinea; time-series; Entwicklungshilfe; Intertemporale Allokation; Papua-Neuguinea